2014
DOI: 10.3168/jds.2013-7744
|View full text |Cite
|
Sign up to set email alerts
|

Raw milk from vending machines: Effects of boiling, microwave treatment, and refrigeration on microbiological quality

Abstract: In Italy, the sale of raw milk from vending machines has been allowed since 2004. Boiling treatment before its use is mandatory for the consumer, because the raw milk could be an important source of foodborne pathogens. This study fits into this context with the aim to evaluate the microbiological quality of 30 raw milk samples periodically collected (March 2013 to July 2013) from 3 vending machines located in Molise, a region of southern Italy. Milk samples were stored for 72 h at 4 °C and then subjected to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 21 publications
5
45
0
2
Order By: Relevance
“…Similarly to L. innocua , pathogenic L. monocytogenes is frequently found in various foodstuffs (Kovacevic et al, 2012; Jami et al, 2014; Ebner et al, 2015; Melo et al, 2015), especially those characterized by pH values higher than 4.4 (CAC, 2009). In the food industry a number of strategies are used to inhibit the growth of undesirable microorganisms, like technological processing (Tremonte et al, 2014), addition of natural substances (Tipaldi et al, 2011; Tremonte et al, 2016), protective microbial cultures (Sorrentino et al, 2013) as well as organic acids (Davidson et al, 2013). Unfortunately, in the case of several food types, sub-lethal pH values may induce resistance mechanisms to acid stress, which make the cells more resistant to severe acid conditions (Gandhi and Chikindas, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to L. innocua , pathogenic L. monocytogenes is frequently found in various foodstuffs (Kovacevic et al, 2012; Jami et al, 2014; Ebner et al, 2015; Melo et al, 2015), especially those characterized by pH values higher than 4.4 (CAC, 2009). In the food industry a number of strategies are used to inhibit the growth of undesirable microorganisms, like technological processing (Tremonte et al, 2014), addition of natural substances (Tipaldi et al, 2011; Tremonte et al, 2016), protective microbial cultures (Sorrentino et al, 2013) as well as organic acids (Davidson et al, 2013). Unfortunately, in the case of several food types, sub-lethal pH values may induce resistance mechanisms to acid stress, which make the cells more resistant to severe acid conditions (Gandhi and Chikindas, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to characterize the psychrotrophic microbiota in milk and to identify the predominant microorganisms after cold storage (Dogan and Boor ; Hantis‐Zacharov and Halpern ; Ercolini and others ; Marchand and others ; Rasolofo and others ; Raats and others ; Tremonte and others ). Hantis‐Zacharov and Halpern () and Raats and others () reported, using culture‐dependent and molecular methods, Pseudomonas , Acinetobacter , and actinobacteria are the dominant groups in Israeli refrigerated milk.…”
Section: Introductionmentioning
confidence: 99%
“…For example, milk may be stored in the door which is likely to be at a higher temperature than the core of the refrigerator (James and James, 2007;Cibin et al, 2013). Tremonte et al (2014) examined raw milk vending machines in southern Italy and found that the milk temperature ranged from 3.5 to 4.1 °C, which was in line with Italian legislation.…”
Section: Temperature Control In Vending Machines and Subsequent Transmentioning
confidence: 54%
“…Other surveys have reported the isolation of pathogens from raw milk sold through vending machines (Giacometti et al, 2012b;Serraino et al, 2013;Gasperetti et al, 2014). Tremonte et al (2014) analysed 30 samples collected from vending machines in southern Italy for indicator microorganisms. In all of the samples, the total mesophilic count (TMC) was around 5 log CFU/mL and increased to over 6 log after 72 hours of storage at 4 °C; counts of Pseudomonas spp.…”
Section: Operation Of Vending Machinesmentioning
confidence: 99%